DISCOVERY LEARNING APPROACH IN IMPROVING ARABIC ABILITY OF PRE-SERVICE TEACHERS IN RELIGIOUS TRAINING CENTRE OF MAKASSAR - Masrariah Amin (Langkawi: Journal of The Association for Arabic and English, 2017)
Discovery Learning can be defined as the learning that takes place when the student is not presented with subject matter in the final form, rather he/she is required to find out the concepts by him/her self. This research aims to describe and analyze discovery learning method to strategically improve the comprehension and reasoning ability of Arabic pre-service teachers, which can motivate and enhance their creativity in order to enrich their insight about Arabic teaching as well, especially those who are in training centre. This research was undertaken in two classes of Makassar Religious Training Centre during June-August 2016. The design of this research is experiment with discovery learning approach with randomized pretest-posttest control group design. It was done randomly when to choosing the participants to be experiment and control group. Based on hypothesis testing, discovery learning has positive effects on the pre-service teachers’ Arabic ability in training centre to understand and analyze Arabic. Therefore, based on two-variance analysis; control and experiment group, there is difference on teachers’ comprehension and reasoning ability in learning Arabic between experiment and control group by using discovery learning and conventional method.